Development of comic page creator media based on Tumbuhkan, Alami, Namai, Demonstrasikan, Ulangi, Rayakan (TANDUR) learning for elementary school students - Nurul Hermiyati; Herlina Usman; Nurafiah Rizkiyani; Lilik Fitriani (Universitas Kanjuruhan Malang, 2023)
The demands of a teacher in this modern era in educating the nation's generation must be able to master IT to support effective learning activities. Data collection techniques used in this study were interviews, preliminary studies, observation, questionnaire collection, and documentation. This development research has gone through the validation stage with the acquisition of an average score of 96.36% from media experts with the criteria of